2004
DOI: 10.1021/ja045631y
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution NMR Spectroscopy of Membrane Proteins in Aligned Bicelles

Abstract: High-resolution solid-state NMR spectra can be obtained from uniformly (15)N-labeled membrane proteins in magnetically aligned bicelles. Fast uniaxial diffusion about the axis of the bilayer normal results in single-line spectra that contain the orientational information necessary for protein structure determination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
186
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(198 citation statements)
references
References 24 publications
10
186
2
Order By: Relevance
“…These results are directly transferable to 2D SLF studies of 15 N nuclei, where they are typically applied for structural measurements on uniformly 15 N labeled membrane proteins. Furthermore, with a simple modification in the 2D PDLF sequence, we demonstrate that, in addition to 1 H-13 C couplings, remote 13 C-31 P and 1 H-31 P couplings from phospholipids can be measured in bicelles. It should be mentioned here that the 2D PDLF pulse sequence has been used in previous studies to obtain high-resolution SLF spectra of solids by overcoming the difficulties found when multiple protons are coupled with a 13 C nucleus.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations
“…These results are directly transferable to 2D SLF studies of 15 N nuclei, where they are typically applied for structural measurements on uniformly 15 N labeled membrane proteins. Furthermore, with a simple modification in the 2D PDLF sequence, we demonstrate that, in addition to 1 H-13 C couplings, remote 13 C-31 P and 1 H-31 P couplings from phospholipids can be measured in bicelles. It should be mentioned here that the 2D PDLF pulse sequence has been used in previous studies to obtain high-resolution SLF spectra of solids by overcoming the difficulties found when multiple protons are coupled with a 13 C nucleus.…”
Section: Introductionmentioning
confidence: 90%
“…The unique feature of WIM and BLEW spinlocking is that they create an isotropic mixing dipolar coupling Hamiltonian, and therefore the corresponding 2D sequences are called HIMSELF. [54][55][56] In a PDLF experiment, where each pair-wise 13 C-1 H spin interaction in a 13 CH n spin system results in a separate doublet, the observed dipolar splitting Δv is related to the coupling constant d simply by Δv = 2kd; k = 0.42 is the scaling factor of the homonuclear decoupling sequence BLEW-48, this value was calibrated using a 2D 1 H/ 13 C HETCOR experiment and closely matched the theoretically predicted value of 0.424. 39 Therefore, the measurement of heteronuclear dipolar couplings is straightforward using this 2D experiment.…”
Section: Two-dimensional 13 C Separated-local-field Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…The sample of Pf1 coat protein in magnetically aligned bilayers was prepared as described previously [32,33]. The phospholipids were 1,2-dimyristoyl-sn-glycero-3-phospho-choline (DMPC) and 1,2-di-O-hexyl-sn-glycero-3-phospho-choline …”
Section: Samplesmentioning
confidence: 99%